Negative-wear super-wear-resistant current-carrying friction pair material

By constructing Ga@Al nanoparticle conductive lubricating film in the current-carrying friction sub-material, arc ablation and mechanical wear problems under current-carrying friction conditions are solved, and super wear resistance with low friction coefficient and negative wear is achieved, which improves the stability and life of conductive contact parts.

CN120400742AActive Publication Date: 2025-08-01LANZHOU INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES

Patent Information

Application Number
CN202510575682.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-05-06
Publication Date
2025-08-01
Estimated Expiration
2045-05-06

AI Technical Summary

Technical Problem

The existing current-carrying friction pair materials have arc ablation and mechanical wear problems under current-carrying friction conditions, resulting in limited service life and stability of conductive contact components.

Method used

Ga@Al nanoparticles with core-shell-covered structures composed of Ga-based liquid metal, Mo coating and Al alloy tampon were prepared by explosion spraying technology on CuCrZr alloy substrate, and a conductive lubricating film was constructed in situ under current-carrying friction conditions.

Benefits of technology

It achieves low coefficient of friction and negative wear effects under a wide range of current and voltage, and has excellent lubrication, wear resistance, high temperature ablation resistance and high conductivity, extending the service life of conductive contact parts.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120400742A_ABST
    Figure CN120400742A_ABST
Patent Text Reader

Abstract

The invention relates to a negative-wear super-wear-resistant current-carrying friction pair material which is a conductive lubricating film which is constructed in situ and stably exists under a current-carrying friction condition, and the current-carrying friction pair material is composed of Ga-based liquid metal, a Mo coating and an Al alloy bolt. Through cooperation of friction pair materials, a friction interface reaction is adjusted to generate a conductive lubricating film, and excellent lubricating and wear-resisting properties are achieved; in a large voltage and current range, the average friction coefficient is always maintained to be 0.25 or below, the existence of the lubricating film enables the surface to present negative wear, and the average negative wear rate is 1.28 * 10 <-6 > mm < 3 > / Nm or above. The obtained material is suitable for application in the field of electric contact industry and provides lubrication and wear protection for the surfaces of mechanical parts.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical fields of lubricating materials and near-zero wear technology, and particularly relates to a super wear-resistant current-carrying friction pair material with negative wear. Background Art

[0002] Current-carrying friction refers to passing direct current with a voltage value of 0 - 50 V and a current value of 0 - 20 V through the friction contact surfaces respectively during the friction process. Different from traditional friction conditions, the current-carrying friction pair exhibits a coupling damage mechanism characterized by mechanical wear, corrosive wear, and arc ablation under the combined action of a mechanical friction system and an electrical contact system. Usually, problems such as arc ablation and Joule heat accumulation are likely to occur during the current-carrying friction process. Therefore, the electrical contact interface is required to have high electron transfer ability and performance of resisting arc ablation wear. Developing a system with both electrical conductivity and lubrication performance is the key technology for developing high-performance current-carrying friction pairs.

[0003] The main technical difficulties in realizing the protection and low wear of the material surface under current-carrying friction conditions are to suppress arc ablation and mechanical wear. There are serious problems such as wear, softening, oxidation, and ablation on the material surface during current-carrying friction. The design of traditional current-carrying friction pairs is mainly conductive soft metal materials and lubricating greases with poor electrical conductivity, which have problems of poor high-temperature mechanical properties under high-load and high-speed conditions and arc breakdown of the organic lubricating film under high-current working conditions, resulting in continuous wear in the sliding contact area during friction, seriously affecting the service life and stable operation of electrical contact components.

[0004] Chinese Patent CN118516586A discloses a TiB2-reinforced Cu-based composite material, which has good electrical conductivity and a low friction coefficient, but its current-carrying wear resistance is poor. Chinese Patents CN118085941A and CN119286571A respectively disclose a lubricating oil-fatty amide and an amide-based conductive lubricating grease, which significantly reduce the friction coefficient of the material, but the organic lubricating film still has difficulty in overcoming the problems of its own low melting point, low bearing capacity, and intolerance to arc ablation. Chinese Patents CN119811738A and CN119812812A use Ga-based liquid metals with different viscosities as conductive lubricating phases, enabling the friction contact surfaces to obtain excellent electrical conductivity and lubrication performance, but the wear rate of the counter-material under current-carrying friction conditions is always high. Summary of the Invention

[0005] The technical problem to be solved by the present invention is to provide a super wear-resistant current-carrying friction pair material with good performance and negative wear.

[0006] To solve the above problems, a super wear-resistant current-carrying friction pair material with negative wear according to the present invention is characterized in that: the current-carrying friction pair material is a conductive lubricating film stably existing under current-carrying friction conditions constructed in-situ, and is composed of a Ga-based liquid metal, a Mo coating and an Al alloy bolt.

[0007] The current-carrying friction pair material is mainly composed of Ga@Al nanoparticles with a core-shell structure.

[0008] The Mo coating is prepared by the following method: using the detonation spraying technique, depositing Mo powder on the surface of a CuCrZr alloy substrate, and obtaining it after natural cooling.

[0009] The conditions of the detonation spraying refer to that the oxygen-fuel ratio is set to 1:1, the gas charging amount is set to 60%, and the spraying distance is adjusted to 200 mm.

[0010] The Al alloy bolt is prepared by the following method: processing 7075 aluminum alloy raw materials into a bolt with a length of 27 mm, a diameter of 6 mm, and a hemispherical end.

[0011] A preparation method of a super wear-resistant current-carrying friction pair material with negative wear as described above is characterized in that: the Mo coating is first polished, then treated with a HCl solution with an ion concentration of 0.1 mol / L for impurity removal, and then the Ga-based liquid metal is dropped onto the surface of the Mo coating, and the positions of the Al alloy bolt and the coating are adjusted until their surfaces are completely immersed in the Ga-based liquid metal to obtain the conductive lubricating film. + The present invention has the following advantages compared with the prior art:

[0012] 1. The present invention combines the protection of the surface of mechanical components by the Mo coating and the conductive lubrication characteristics of the liquid metal, and invents a conductive friction pair material showing negative wear under current-carrying friction conditions. 2. By in-situ constructing a conductive lubricating film on the surface of the coating, the current-carrying friction pair of the present invention has excellent lubrication, wear resistance, high-temperature ablation resistance and high conductivity and other properties, overcoming the design defects of traditional soft metals and conductive lubricating greases under current-carrying friction conditions.

[0013] 3. The super wear-resistant current-carrying friction pair material of the present invention has excellent friction reduction and wear resistance effects. While ensuring the current transmission efficiency, by isolating the contact between the coating and the Al alloy bolt, it realizes wear-free protection of the material surface and macroscopic negative wear.

[0014]

[0015] ​4. The excellent lubrication and wear resistance mechanisms of the super wear-resistant current-carrying friction pair material of the present invention are as follows: under the action of current and friction, a wear-resistant lubricating film composed of Ga@Al nanoparticles with a core-shell coating structure will be rapidly formed on the surface of the Mo coating introducing Ga-based liquid metal.

[0016] 5. The Mo coating prepared by using the explosion spraying technology included in the present invention has a dense structure, good mechanical properties and electrical conductivity, providing strong support for negative wear and super wear-resistant performance under current-carrying friction conditions.

[0017] 6. The super wear-resistant current-carrying friction pair material of the present invention has good lubrication and anti-wear performance under high speed, heavy load and large current voltage. It has excellent tribological properties within a wide current-carrying range of voltage from 0 to 50 V and current from 0 to 20 A. The friction coefficient always remains below 0.25; almost no wear occurs on the coating surface, so that negative wear phenomenon appears in the presence of a stable lubricating film.

[0018] 7. The super wear-resistant current-carrying friction pair material of the present invention still achieves excellent electrical conductivity and negative wear effect at relatively high voltage (50 V) and current (20 A) levels, and the negative wear amount increases within a certain range with the increase of voltage and current, and the protection effect is enhanced.

[0019] 8. The Ga-based liquid metal, Mo coating and Al alloy bolt selected in the present invention are all commonly used materials in the fields of conductive wear resistance and lubrication; the preparation method of the Mo coating is simple and fast. At the same time, the manufacturing cost required for the system is relatively low, which is suitable for applications in the field of electrical contact industry and provides lubrication and wear protection for the surface of mechanical parts.

[0020] 9. Using the material of the present invention provides key technical reserves for the long-term service of conductive materials under current-carrying conditions in the power and electronics fields and the reliability of mechanical equipment. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] The following further describes in detail the specific embodiments of the present invention with reference to the drawings.

[0022] Figure 1 It is the cross-sectional morphology of the Mo coating of the present invention.

[0023] Figure 2 It is the average friction coefficient and wear rate varying with voltage of the present invention.

[0024] Figure 3 It is the average friction coefficient and wear rate varying with current of the present invention.

[0025] Figure 4 It is the cross-sectional morphology of the lubricating film of the present invention.

[0026] Figure 5 This is the magnified morphology of the Ga@Al nanoparticles inside the lubricating film of the present invention. Detailed implementation manners

[0027] The negative wear described in the present invention refers to the phenomenon that the surface of the material is hardly worn, and due to the formation of the lubricating film, the wear amount is negative.

[0028] A super wear-resistant current-carrying friction pair material with negative wear. This current-carrying friction pair material is an in-situ constructed conductive lubricating film that stably exists under current-carrying friction conditions, and is composed of a Ga-based liquid metal, a Mo coating, and an Al alloy bolt. This current-carrying friction pair material is mainly composed of Ga@Al nanoparticles with a core-shell structure.

[0029] Among them: The Mo coating is prepared as follows: Using the detonation spraying technique, deposit Mo powder on the surface of the CuCrZr alloy substrate, and obtain it after natural cooling. The conditions for detonation spraying refer to that the oxygen-fuel ratio is set to 1:1, the gas charging amount is set to 60%, and the spraying distance is adjusted to 200 mm.

[0030] The Al alloy bolt is prepared as follows: Process the 7075 aluminum alloy raw material into a bolt with a length of 27 mm, a diameter of 6 mm, and a hemispherical end.

[0031] Under different current-carrying and high-load high-speed friction working conditions within the voltage range of 0 - 50 V and the current range of 0 - 20 A for the material obtained in the present invention, the friction coefficient always remains below 0.25, and lubrication and negative wear performance can be achieved under any current-carrying friction condition.

[0032] The preparation method of this super wear-resistant current-carrying friction pair material: First, polish the Mo coating, then use a H + HCl solution with an ion concentration of 0.1 mol / L for impurity removal, and then drop the Ga-based liquid metal onto the surface of the Mo coating, and adjust the positions of the Al alloy bolt and the coating until their surfaces are completely immersed in the Ga-based liquid metal to obtain the conductive lubricating film.

[0033] Examples The current-carrying friction pair material is composed of three parts: a Ga-based liquid metal, a Mo coating, and an Al alloy bolt. The material can in-situ construct a conductive lubricating film that stably exists under current-carrying friction conditions, and is mainly composed of Ga@Al nanoparticles with a core-shell structure. Among them, the Ga@Al nanoparticles mainly originate from the penetration of the Ga-based liquid metal into the grain boundaries of the Al alloy, the encapsulation of the nanoparticles, and the reconstruction on the surface of the Mo coating.

[0034] By Figure 4It can be seen that the coating surface is flat and hardly worn. The thickness of the lubricating film is about 1 μm, and it is composed of Ga@Al nanoparticles inside, forming a relatively dense composite structure. From Figure 5 It can be seen that the Ga@Al nanoparticles inside the lubricating film have typical core-shell structure characteristics. The outer Ga-based liquid metal mainly provides lubrication and electrical conductivity, while the internal nanoparticles mainly provide mechanical load-bearing performance.

[0035] Preparation of Mo coating: Using the detonation spraying technique, Mo powder is deposited on the surface of the CuCrZr alloy substrate. During spraying, the oxygen-fuel ratio is set to 1:1, the gas charging amount is set to 60%, and the spraying distance is adjusted to 200 mm. After natural cooling, the Mo coating is obtained. As shown in Figure 1, it can be seen that the coating thickness is 310 μm, the internal structure is dense, and it is well combined with the CuCrZr alloy substrate.

[0036] Preparation of Al alloy bolt: The 7075 aluminum alloy raw material is processed into a bolt with a length of 27 mm, a diameter of 6 mm, and a hemispherical end.

[0037]

Friction without electric current

[0038] Before the friction test, the pollutants and impurity oxides on the surface of the polished Mo coating sample are removed using HCl solution. After surface cleaning, 2 g of Ga-based liquid metal is dropped onto the surface of the Mo coating sample. Adjust the positions of the Al alloy bolt and the coating until their surfaces are completely immersed in the Ga-based liquid metal.

[0039] During the friction experiment, a normal stress of 30 N is applied, the reciprocating frequency of the test bench is 13 Hz, and the reciprocating length is 5 mm. When the surfaces start to contact and reach the predetermined load and reciprocating speed, the DC power supply is not turned on, serving as a control group. The friction experiment is carried out at room temperature (25 °C), and the test time is 30 minutes. The friction coefficient during the test process is automatically recorded by the computer, and then the average friction coefficient is calculated by the software. A non-contact optical three-dimensional profiler is used to measure the three-dimensional topography and wear rate of the worn surface.

[0040] Test results: The average friction coefficient is 0.22 ± 0.04, and the average negative wear rate is 1.79 ± 0.53 × 10 - 6 mm 3 / Nm.

[0041]

Friction with variable voltage and electric current

[0042] Before the friction test, the pollutants and impurity oxides on the surface of the polished Mo-coated sample were removed using HCl solution. After the surface cleaning treatment, 2 g of Ga-based liquid metal was dropped onto the surface of the Mo-coated sample. The positions of the Al alloy bolt and the coating were adjusted until their surfaces were completely immersed in the Ga-based liquid metal.

[0043] During the friction experiment, a normal stress of 30 N was applied, the reciprocating frequency of the test bench was 13 Hz, and the reciprocating length was 5 mm. When the surfaces began to contact and reached the predetermined load and reciprocating speed, the DC power supply was turned on, and a current of the set value flowed through the contact surface between the Al alloy bolt and the coating, forming a closed circuit in the friction system. Current-carrying conditions: The fixed current value was 10 A, and the voltage values were set to 10 V, 30 V, and 50 V respectively. All friction experiments were carried out at room temperature (25 °C), and the test time was 30 minutes. The friction coefficient during the test was automatically recorded by the computer, and then the average friction coefficient was calculated by the software. A non-contact optical three-dimensional profiler was used to measure the three-dimensional topography and wear rate of the worn surface.

[0044] The test results are shown in Table 1 and Figure 2 as follows.

[0045] Table 1 Friction coefficient and wear rate As the voltage increased to 30 V, the friction coefficient continuously decreased from 0.21 to 0.18. When the voltage reached 50 V, the friction coefficient instead increased to 0.24; as the voltage continued to increase, the negative wear accumulation on the surface increased from 1.79 × 10 -6 mm 3 / Nm to 3.40 × 10 -6 mm 3 / Nm.

[0046]

Current-carrying friction with variable current

[0047] Before the friction test, the pollutants and impurity oxides on the surface of the polished Mo coating sample were removed using an HCl solution. After surface cleaning, 2 g of Ga-based liquid metal was dropped onto the surface of the Mo coating sample. The positions of the Al alloy bolt and the coating were adjusted until their surfaces were completely immersed in the Ga-based liquid metal.

[0048] During the friction experiment, a normal stress of 30 N was applied, the reciprocating frequency of the test bench was 13 Hz, and the reciprocating length was 5 mm. When the surfaces began to contact and reached the predetermined load and reciprocating speed, a DC power supply was turned on, and a current of a set value flowed through the contact surface between the Al alloy bolt and the coating, forming a closed circuit in the friction system. Current-carrying conditions: The fixed voltage value was 30 V, and the current values were set to 5 A, 15 A, and 20 A respectively. All friction experiments were carried out at room temperature (25 °C), and the test time was 30 minutes. The friction coefficient during the test was automatically recorded by the computer, and then the software calculated the average friction coefficient. A non-contact optical three-dimensional profiler was used to measure the three-dimensional topography and wear rate of the worn surface.

[0049] The test results are shown in Table 2 and Figure 3 as follows.

[0050] Table 2 Friction Coefficient and Wear Rate As the current continuously increased from 5 A to 20 A, the average friction coefficient always remained between 0.15 and 0.20, and the average friction coefficient was the smallest at 5 A; as the voltage continuously increased, the negative wear accumulation on the surface increased from 1.79 × 10 - 6 mm 3 / Nm to 2.73 × 10 -6 mm 3 / Nm. Both the friction coefficient and the negative wear showed a trend of first increasing and then decreasing with the current.

[0051] It can be understood that the above embodiments are exemplary and should not be construed as limitations on the present invention. Any changes, modifications, substitutions, and variations made by those of ordinary skill in the art to the above embodiments are within the protection scope of the present invention.

Claims

1. A super wear-resistant current-carrying friction pair material with negative wear, characterized in that: The current-carrying friction pair material is a conductive lubricating film that stably exists under current-carrying friction conditions and is in-situ constructed, and is composed of Ga-based liquid metal, Mo coating and Al alloy bolt.

2. The super wear-resistant current-carrying friction pair material with negative wear as described in claim 1, characterized in that: The current-carrying friction pair material is mainly composed of Ga@Al nanoparticles with a core-shell structure.

3. The super wear-resistant current-carrying friction pair material with negative wear as described in claim 1, characterized in that: The Mo coating is prepared by the following method: using the explosion spraying technology, depositing Mo powder on the surface of the CuCrZr alloy substrate and then obtaining it after natural cooling.

4. The super wear-resistant current-carrying friction pair material with negative wear as described in claim 3, characterized in that: The conditions of the explosion spraying refer to that the oxygen-fuel ratio is set to 1:1, the gas filling amount is set to 60%, and the spraying distance is adjusted to 200 mm.

5. The super wear-resistant current-carrying friction pair material with negative wear as described in claim 1, characterized in that: The Al alloy bolt is prepared by the following method: processing the 7075 aluminum alloy raw material into a bolt with a length of 27 mm, a diameter of 6 mm and a hemispherical end.

6. The preparation method of a negative wear ultra-wear-resistant current-carrying friction pair material according to any one of claims 1 to 5, characterized in that: The Mo coating was first polished, and then the impurities were removed with an HCl solution with an ion concentration of 0.1 mol / L. Then, the Ga-based liquid metal was dropped onto the surface of the Mo coating, and the positions of the Al alloy bolt and the coating were adjusted until their surfaces were completely immersed in the Ga-based liquid metal to obtain the conductive lubricating film. + ​

Citation Information

Patent Citations

  • Application of copper-containing friction pair in improving wettability and / or lubricating property of gallium-based liquid metal

    CN117840426A

  • Gallium-based liquid metal lubricant for copper-aluminum friction pair as well as preparation and application of gallium-based liquid metal lubricant

    CN118667595A

  • Conductivity-enhanced current-carrying friction pair coating material as well as preparation method and application thereof

    CN118685770A

  • Composite coating and application thereof in improving wettability of liquid metal to surface of solid matrix

    CN118910550A

  • Liquid metal bearing with high sealing performance

    CN119146156A

Cited By

  • Current-carrying intelligent lubricating paint, current-carrying intelligent lubricating coating and preparation method thereof

    CN121249241A

  • Current-carrying intelligent lubricating coating, current-carrying intelligent lubricating coating and preparation method thereof

    CN121249241B

  • Hard inorganic particle reinforced aluminum alloy surface composite coating and preparation method thereof

    CN121555949A

  • A hard inorganic particle reinforced aluminum alloy surface composite coating and a method for preparing the same

    CN121555949B